Prenatal Diagnosis of a Congenital Postaxial Longitudinal Limb Defect: A Case Report - Joana Pauleta; Maria Antonieta Melo; Luís Mendes Graça (Obstetrics and Gynecology International)
Introduction. Although congenital longitudinal fibular deficiency is one of the most common long bone deficiencies, there are few published cases of its prenatal diagnosis. Case report. A right longitudinal deficiency of the fibula associated with tibial shortening, foot equinovalgus, and absence of the fourth and fifth foot rays diagnosed at 22 weeks gestation is described. Sequential ultrasonographic surveillance was performed without obstetric complications. The anomaly was confirmed after birth, and conservative orthopaedic management was decided. Conclusion. Though rarely seen, postaxial longitudinal limb defect may be detected by ultrasound. The correct approach can only be decided after birth, when the functional impact of the anomaly can be fully evaluated.